Public Participation in the Social Science: A Systematic Literature Review - Muhammad Ainul Usama; Ulung Pribadi; Al Fauzi Rahmat (Universitas Medan Area, 2021)
Public participation is the right and obligation of citizens to contribute to development by contributing to initiative and creativity. Public participation has also attracted a lot of attention from academia as a concept of public policy. The authors conducted a systematic literature review of published articles in the social sciences to enhance our understanding of public participation. Some of the main issues are explained in this area through the NVIVO 12 plus software that qualitative analysis tool. The main issues are community, development, government, information, and interests. This article raises several propositions on the matter. This article suggests some new topics for further research.